2017
DOI: 10.1016/j.jid.2017.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Research Techniques Made Simple: High-Throughput Sequencing of the T-Cell Receptor

Abstract: High-throughput sequencing (HTS) of the T-cell receptor (TCR) has advanced rapidly in recent years, giving the unique opportunity to identify and quantify every distinct T-cell clone present within any biological sample. This sensitive and accurate technique provides the relative frequency of each individual clone within the full T-cell repertoire, allowing to study particular single T-cell clones of interest as well as the concomitant analysis of all different clones of the whole population. HTS is essential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 10 publications
(11 reference statements)
0
32
0
Order By: Relevance
“…It is also worth mentioning here that virus shedding in some patients may continue for some days after symptom relief and recovery [33,34]. Notably, a very recent study showed that the communicable period (expressed as first time of SARS-CoV-2 positive to date of virus clearance) in patients infected by SARS-CoV-2 was 6 days (IQR, 2-12 days) in subjects without symptoms compared to 12 days (IQR, [12][13][14] in those who became instead symptomatic [35].…”
Section: Diagnostic Accuracymentioning
confidence: 94%
See 2 more Smart Citations
“…It is also worth mentioning here that virus shedding in some patients may continue for some days after symptom relief and recovery [33,34]. Notably, a very recent study showed that the communicable period (expressed as first time of SARS-CoV-2 positive to date of virus clearance) in patients infected by SARS-CoV-2 was 6 days (IQR, 2-12 days) in subjects without symptoms compared to 12 days (IQR, [12][13][14] in those who became instead symptomatic [35].…”
Section: Diagnostic Accuracymentioning
confidence: 94%
“…injury exposure, unreliable cold chain, prolonged transportation time), presence of interfering substances (e.g. release of cellular components that may interfere with the assay due to whole blood freezing, use of inappropriate additives) [13][14][15], as well as by a number of procedural issues occurring during sample preparation, thus including pipetting errors during manual sample preparation or aliquoting, cross-contamination and sample mismatch, among others [16]. The leading specific problems that may plague the quality of RT-PCR assays include sample contamination (even trace amounts of external DNA may jeopardize test results) and testing carried out in patients receiving antiretroviral therapy, which may then generate falsenegative results [15].…”
Section: Preanalytical Errorsmentioning
confidence: 99%
See 1 more Smart Citation
“…To limit sampling error, small clusters of 10 to 20 atypical Analysis of TCRg rearrangements in microdissected mycosis fungoides samples. H&E-stained skin sections were microdissected using a laser microscope to capture small clusters of atypical "tumor" cells (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Examples of stained skin sections used for LCM are provided in Supplementary Fig.…”
Section: Tcr Repertoire In Microdissected Mycosis Fungoides Cellsmentioning
confidence: 99%
“…I have also continued to benefit by reading the wide breadth of topics that include some privileged access to pearls of advice not shared within standard scientific publication. Examples include the comparison of different approaches to T-cell receptor analysis (Matos et al, 2017) and the practical experimental rationale to guide the choice of labeling enzymes in methods to elucidate protein interactions through spatial proximity (Che and Khavari, 2017). The bullet points of limitations to each technique hold helpful cautions and are refreshingly frank.…”
mentioning
confidence: 99%